Nurturing a network of policy analysts for enhanced agricultural development and food and nutrition security in Kenya - Karugia, Joseph T. (International Livestock Research Institute, 2018)
ILRI (www.ilri.org) works to improve food and nutritional security and reduce poverty in developing countries through research for efficient, safe and sustainable use of livestock. It is the only one of 15 CGIAR research centers dedicated entirely to animal agriculture research for the developing world. Co-hosted by Kenya and Ethiopia, it has regional or country offices and projects in East, South and Southeast Asia as well as Central, East, Southern and West Africa. The AgriFoSe2030 Program was developed by a consortium of scientists from the Swedish University of Agricultural Sciences (SLU), Lund University, Gothenburg University and Stockholm Environment Institute and hosted by the SLU Global (Agricultural Sciences for Global Development) platform. AgriFose2030 targets the Sustainable Development Goal Number 2 (SDG2) in low-income countries through a science-based approach on local, regional and global scales. SDG2 aims at ending hunger, achieving food security, improving nutrition and promoting sustainable agriculture. AgriFoSe2030 contributes to sustainable intensification of agriculture for increased food production on existing agricultural land; the aim is to do so by transforming practices toward more efficient use of human, financial and natural resources. It translates state-of-the–art science for supporting better policies and improved practices within the agricultural sector. This translation is achieved through a set of activities, some of which aim to improve the capacity to synthesize and translate science into information that is directly applicable, and some are about performing this translation per se. This is the final report that covers the period from October 2017 to 31 October 2018.